Masificación del judo como iniciación deportiva en la Liga parroquial de Puerto Bolívar año 2012 - Martínez Miranda, Nelly Alexandra (2015)
This thesis "massification of judo as sport initiation in the Parish Port Bolivar league 2012". It was developed by the need to contribute to the community effort to develop their physical skills through sports discipline Marcial practice judo in the same denomidada proposal has a seminar - workshop for beginners judo as a political strategy for mass sports league in the parish of port Bolivar, its object is motivated following verify that the place where the investigation did not have trained personnel in this sport.